DEVELOPMENT OF INDEPENDENT RESEARCH SKILLS AND CREATIVE ABILITIES OF STUDENTS - Yuldasheva N.M. (Лучшие интеллектуальные исследования, 2023)
Abstract: Paper examines the methods and strategies used in education to foster the development of students' research skills and creative abilities. The article discusses practical aspects of education that stimulate curiosity and innovation. The authors highlight key methodologies and approaches that contribute to the cultivation of critical thinking and the ability to independently seek and analyze information.